The Role Of Sustainability Performance By Motivation And Environment Case Study At PP. London Sumatera - Pallawagau, Andi; Asyari; Muhammad., Ramli (CV ODIS, 2025)
Employee performance at PP London Sumatra is characterized by the quality of public services which will be the main focus where the speed of administration and service efficiency will be greatly assisted by the existence of a computerized service system that has been jointly developed. The aim of the research is to analyze the influence of work motivation on employee performance and the work environment on employee performance. sample of 85 employees with linear regression analysis test as a research measuring tool. Research data uses a questionnaire. data analysis to test the hypothesis using t test analysis. and R square test. The research results found a significant relationship between motivation and employee performance and the work environment also had a significant positive effect on employee performance